Innovative Pedagogy in Remote Papua: Enhancing Catholic Teachers’ Competencies through Challenge-Based Learning in Keerom - Evaristus Silitubun (Universitas Nurul Jadid, 2025)
Keerom Regency in Papua, Indonesia, is a remote area facing significant geographical, social, and cultural challenges. Limited access to educational resources and a lack of professional training opportunities for Catholic religious education teachers have contributed to the low quality of teaching. Moreover, the scarcity of contextually relevant teaching materials makes it difficult for teachers to deliver lessons that connect with students' daily lives. This community service project aimed to enhance teachers’ competencies through a workshop on developing teaching modules based on the Case-Based Learning (CBL) approach. The program used a quasi-experimental method with pre-tests and post-tests to measure the improvement in participants’ pedagogical skills. The training combined theoretical concepts and practical sessions, emphasizing the development of CBL-based teaching modules relevant to students’ social, cultural, and religious contexts. The results showed a significant increase in teachers’ competence, with post-test scores improving by 80% compared to the pre-test results. The participants’ active engagement and enthusiasm throughout the training further demonstrated the success of the program. This initiative contributed not only to improving teachers’ skills but also to enhancing the overall quality of Catholic religious education in remote areas. Sustainable implementation requires ongoing training and adequate educational support.